Drugačna metoda določevanja koncentracij plinov zaprtih prostorov v odvisnosti od časa - Likar, Jakob (Strojniški vestnik, 2001)
This paper proposes an alternative approach to the ventilation design of enclosed and half enclosed underground structures, where more detailed analysis is required. Theoretical basics are represented and the area of application is determined. To show the advantage of such approach a calculation of movement of exhausted air through enclosed structure as function of time has been executed.
Keywords: prezračevalne naprave; prezračevanje